KEMAUAN BERJALAN KAKI PENUMPANG ANGKUTAN PERKOTAAN (STUDI KASUS PENUMPANG ANGKUTAN PERKOTAAN DI YOGYAKARTA) - Basuki, Imam (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The size of the quality urban transport services can be divided into two major categories, quantitative measures and qualitative measures. Quantitative aspects of the measures is that the service can be assessed with a number and size of the qualitative measures is an assessment of the difficult aspects of the service can not even expressed in a value size figures. In this paper discussed a way to specify a standard rating scale quantitative research from a desire urban passenger transport in Yogyakarta in terms of walking with a questionnaire based on the values of the existing benchmark values that already exist. Results scale assessment as benchmarks of walking distance for urban passenger transport in Yogyakarta with the level of service A (< 225 meters), the level of service B ( 225-325 meters ), the level of service C ( 325-475 meters ) and the level of service D (>475meters). Results quantitative performance value scale urban transportation, can be made as a benchmark for assessing a condition urban transport areas in other cities along the scale and conditions of a city that is considered similar.